2013
DOI: 10.3109/03639045.2013.858741
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the primary particle size distributions of pressurized metered dose inhalers by using inkjet spray drying for targeting desired regions of the lungs

Abstract: Optimizing the primary particle size distributions of pressurized metered dose inhalers by using inkjet spray drying for targeting desired regions of the lungs http://researchonline.ljmu.ac.uk/625/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In contrast, the Qvar Easi-Breathe is a breath-actuated device that has been devised with a flow-triggered system driven by a spring that automatically releases the dose with the patient's inhalation. 27,28 It was designed to overcome the problem of coordination between actuation and breathing. Actuation of the aerosol occurs at low inhalation flows of approximately 20 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Qvar Easi-Breathe is a breath-actuated device that has been devised with a flow-triggered system driven by a spring that automatically releases the dose with the patient's inhalation. 27,28 It was designed to overcome the problem of coordination between actuation and breathing. Actuation of the aerosol occurs at low inhalation flows of approximately 20 L/min.…”
Section: Discussionmentioning
confidence: 99%
“…1). Ehtezazi et al have reported the instrument design and setup in previous papers [20,21]. Briefly, the inkjet instrument was built using a glass capillary tube, which was already adjusted at one end to form a nozzle orifice of a selected size (50 μm and 20 μm).…”
Section: Liposome Preparation By Inkjet Methodsmentioning
confidence: 99%
“…Inkjet method produces uniform droplets from an inkjet device [18], and this technique has been used to produce uniform liposomes with a size in the range of 20-100 nm [19], uniform respirable particles for the formulation of pharmaceutical inhalers [20,21], and uniform porous polymer particles [22]. For the production of liposomes, the amphiphilic compounds were dissolved in ethanol and printed into an aqueous solution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Inkjet printing methods have been utilised for pharmaceutical applications such as printing drug solutions on edible and conventional papers, manufacturing tablets, personalised medicine, preparation of bio‐adhesives, manufacture of spherical uniform particles and manufacture of uniform and custom shape particles …”
Section: Introductionmentioning
confidence: 99%